The patron-driven library : a practical guide for managing collections and services in the digital age - Allison, Dee Ann K. (Chandos information professional series., 2013)
"A guide for librarians to develop a new relationship with technology that preserves the core mission of libraries while responding to the needs of a new generation of library clients"--Page xxii.